2012
DOI: 10.1183/09031936.00104712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes of Italian and Spanish patients with α1-antitrypsin deficiency

Abstract: With the aim of providing better clinical characterisation of patients with a 1 -antitrypsin deficiency (AATD), we analysed the data of adult patients with severe AATD enrolled in the Spanish and Italian national registries.We assessed 745 subjects, 416 of whom were enrolled in the Spanish registry and 329 in the Italian registry. 57.2% were male and 64.9% were smokers or former smokers with a mean¡SD age of 49.9¡13.8 years. Most (81.2%) were index cases, mainly having the PI*ZZ genotype (73.4%), and the mean¡… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 49 publications
4
40
0
6
Order By: Relevance
“…Our data would contradict these findings, demonstrating that radiologically detected bronchiectasis is both common in AATD and that there is no dependent relationship to emphysema or indeed a history of smoking. This is supported by similar studies on bronchiectasis and emphysema in AATD and also by registry data showing a high prevalence of bronchiectasis in the AATD population in Spain and Italy (14,23). Most people in our study had evidence of mild radiological bronchiectasis with minimal associated clinical symptoms such as increased frequency of cough or pulmonary exacerbation compared to those with emphysema, however those with more severe bronchiectasis did report significantly poorer health status outcomes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our data would contradict these findings, demonstrating that radiologically detected bronchiectasis is both common in AATD and that there is no dependent relationship to emphysema or indeed a history of smoking. This is supported by similar studies on bronchiectasis and emphysema in AATD and also by registry data showing a high prevalence of bronchiectasis in the AATD population in Spain and Italy (14,23). Most people in our study had evidence of mild radiological bronchiectasis with minimal associated clinical symptoms such as increased frequency of cough or pulmonary exacerbation compared to those with emphysema, however those with more severe bronchiectasis did report significantly poorer health status outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…A significant proportion of the severely deficient AATD population in the Irish registry are compound heterozygote PiSZ individuals, a finding reflected in reports from other national registries (14). Despite a growing number of known PiSZ individuals there is a paucity of data in relation to outcomes of this AAT--deficient phenotype (4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In terms of clinical presentation, the average age of our patients (49.9 years) was similar to that reported in studies from Italy, Germany and Spain (45-49 years) and COPD was the most frequent diagnosis ( fig. 3) [19,20].…”
Section: Polandmentioning
confidence: 99%
“…Holme and Stockley confirmed this in a prospective study of individuals identified with physiological discordance (normal FEV 1 and low diffusing capacity and vice versa) [65]. An observational study of 745 patients with severe A1ATD compared subjects with emphysema, chronic bronchitis and asthma overlap [66]. This study found chronic bronchitis patients were younger with a lower number of pack years and had better preserved lung function.…”
Section: Clinical Phenotypesmentioning
confidence: 73%